Metodologia de projeto de controladores de amortecimento para posicionamento parcial de polos de modelos multimáquinas de sistemas de potência - Rossi, Carlos Henrique (2012)
This work proposes a methodology for the design of controller to damp low frequency electromechanical oscillations in power systems. The control problem is structured in the form of matrix inequalities, which allows obtaining a numerical solution for the control problem. The damping controllers based on dynamic output feedback, generated by design methodologies in the form of matrix inequalities, usually presents high order. In addition, the design of this controller, considering large power systems, usually requires excessive computational effort. In this context, this work proposes a methodology for the design of reduced order controllers. The proposed methodology employs a performance index that is less costly in terms of computational effort when compared to the one with the traditional regional pole placement. The adopted performance index for the closed loop system is the energy of the system output. This energy corresponds to the integral of the signal squared regarding the system output. The proposed methodology allows specifying a performance index only for the response modes of interest, overcoming the limitations of the methodologies based on regional pole placement. The relation between the energy value of the output signal of the system and its damping factor is established by means of an algebraic equation. In this paper, the methodology is applied to generate damping controller for synchronous generators. However, the proposed procedure is general enough to be applied to other kinds of power plants (wind generation, for example), to FACTS devices, as well as to other dynamic systems. The methodology has generated an effective controller for a case where the formulation based on the regional pole placement is unable to generate a controller which assures a good stability margin for the response mode of interest.